The Syntax of Clitic Placement in European Portuguese - Barrie, Michael (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2000)
ABSTRACTIn most Romance languages, object clitics appear to the left of the verb (proclitics); in European Portuguese (henceforth, EP) they appear to the right (enclitics). Furthermore, several syntactic environments trigger proclisis in EP, which usually have no effect on clitic placement in other Romance languages. These environments can be roughly split into two categories: those in which CP is filled (Wh-questions, focus constructions, subordinate clauses), and those in which a head position between CP and TP is filled (negation, special adverbs). To account for this, I propose that C0 in EP has the strong feature [+lexical] which must be checked by a lexical item before Spell-Out. I also propose the following clause structure: TopP>CP>AdvsP>NegP>TP>vP>VP. AdvsP is a functional projection which hosts any one of a small set of special adverbials. If CP is filled by Spell-Out (either in its head or specifier position), the [+lexical] feature will be checked and erased. If not, then C0 attracts the closest lexical item.